(untitled) (Medico Legal Update, 2021)
Terror attacks result in prolonged traumatic effects on both victims and survivors. Previous studies have analyzed the effects of terror attacks on the psychological condition of post-traumatic stress disorder from exposure to terrorist attacks. This article discusses victims of terrorism in Indonesia based on data from 2008-2018. The use of data over the span of several years is important to determine the trend of victimization so that a response can be made to reduce the suffering of victims. This perspective also includes counterterrorism efforts to minimize the suffering of victims directly or indirectly due to terrorism. The criminal justice system can also reform paradigmatically, providing fulfillment of the rights of victims in accordance with applicable legal norms.